Cool as a (sea) cucumber? Exploring public attitudes toward seawater air conditioning in Hawai'i. (July 2015) - Lilley, Jonathan; Konan, Denise Eby; Lerner, Darren T.
Highlights: Survey undertaken into public acceptance of seawater air conditioning in Waikīkī. 62% of O'ahu residents support seawater air conditioning, just 7% oppose. When compared to eight other energy options, seawater air conditioning ranks eighth. Concern exists of potential reef damage and algae production. Abstract: Seawater air conditioning (SWAC) has the potential to reduce the energy demand for air conditioning by 75–90%. This article reports the findings of a mail survey sent to residents of the Hawaiian island of O'ahu investigating attitudes toward SWAC and opinions of installing a system in Waikīkī. Results show that while only 55% of O'ahu residents were previously aware of SWAC, 62% supported its development in Waikīkī and just 7% opposed. Of those familiar with the technology, support rose to 69%. However, when compared to eight other low-carbon energy options, SWAC ranked second to last. Concern exists about the potential environmental impacts of SWAC, particularly with regard to reef damage and algae production. Logistic regression analysis shows no significant difference in the likelihood of a person supporting SWAC due to their sex or level of education; although age, political affiliation, and locality do affect the likelihood of support. Those who see tourism as very important to Hawai'i and think SWAC will benefit the tourism industry are more likely to support, along with those who have a very positive opinion of renewable energy, and those who are familiar with the technology. In contrast, high-income O'ahu residents are less likely to support SWAC.